Design and Build a Control and Monitoring System in a Cat Cage Based on the Internet of Things (IoT) (Case Study in Violet Pet Shop & Clinic) - Bestari, Karina Bella; Mustafa, Lis Diana; Junus, Mochammad (Politeknik Negeri Malang, 2023)
Violet Pet Clinic & Shop is a place to day care and care for pets such as cats which is located at Jalan Borobudur No.11, Mojolangu, Kec. Lowokwaru, Malang City, East Java Province. At Violet Pet Clinic & Shop, it provides various facilities including grooming, day care, doctor consultation, and ultrasound. The type of research carried out includes the type of development research, which functions to produce certain products and test product effectiveness. Equipment testing results show good performance. The tools developed can be a solution to problems at Violet Pet Shop & Clinic. The temperature sensor has an average reading error of 0.88 percent with an accuracy percentage of 99.12 percent, the ESP32 camera can capture images properly. In one of the control systems, feeding in large quantities with a feed dose weighing 150g can only provide 4 times of feed with a delay of 10 seconds.